The Asanté™ HIV-1 Rapid Recency® Assay is reliable, feasible, and acceptable for use at the point-of-care in Lusaka, Zambia - Shilpa S. Iyer; Jake M. Pry; Herbert Kapesa; Misinzo Moono; Chilambwe Mwila; Christiana Frimpong; Mirriam Nanyangwe; Lumbani Phiri; Ruth Ngandu; Precious Sakanya; Sharon Mwansa; Talandila Phiri; et al. (PLoS ONE, 2026)
Background Zambia established a recent infection testing algorithm (RITA) incorporating a novel point-of-care (POC) rapid test—the Asanté™ HIV-1 Rapid Recency® Assay (RTRI)—plus a HIV-1 viral load (VL) test to distinguish recent (≤12 months) from long-term (>12 months) HIV acquisition. This study evaluated the field performance of RTRI when implemented by healthcare workers at the POC. Methods We enrolled individuals newly diagnosed with HIV between 20 May 2021 and 10 March 2022 at two Ministry of Health facilities in Lusaka, Zambia. Participants received on-site RTRI testing and provided an additional sample for repeat RTRI and VL testing at a central laboratory. Final recent infection testing algorithm (RITA) results were returned to the study sites and were made available to clients at their study follow-up visit. Agreement between POC- and laboratory-RTRI was assessed using Cohen’s Kappa. We compared recent versus long-term HIV classification across testing locations using the national RITA as the reference standard. Four focus group discussions (FGDs) with health staff explored perceptions surrounding POC-RTRI implementation. Results Agreement between POC and laboratory RTRI was 96.5%, with a Kappa of 0.812 (95% CI: 0.704–0.920). The POC-RTRI results indicated numerically more recent infections than laboratory-RTRI (30 vs 27), with three POC-RTRI false positives resulting in reduced sensitivity 85.0% for the POC-RTRI compared to 100.0% sensitivity for the laboratory-RTRI against the RITA reference standard. FGD participants (n = 28) agreed that POC RTRI was feasible and acceptable with adequate training, human resources, client counselling, and quality assurance measures. Conclusion There was strong concordance between POC- and laboratory-RTRI results. The findings support the feasibility of implementing RTRI at POC by non-laboratory health workers, provided adequate training and health system resources are in place.